PERAN ORANG.TUA DALAM. PERKEMBANGAN .SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI RA MIFTAHUL HUDA KECAMATAN KARANGPLOSO (Jurnal Dewantara, 2021)
The role of parents determines the development of children, especially their social emotional development. The of this study was to describe the social-emotional condition of RA Miftahul Huda's children,  describe the role of parents in children's social-emotional development and to identify the factors that influence children's social-emotional development. This study uses a qualitative descriptive approach. Data techniques used are observation, interviews, and documentation. The results showed that the condition of children's social-emotional development developed as expected and some children had not yet developed. The role parents is very important in the social emotional development children, parents as the main and first educators for children. Factors that influence the social emotional development of children are from the environment, family, early social experiences of children.